The Effect of Job Stress and Job Insecurity on Turnover Intention at PT. Pelindo Multi Terminal - Alexander Sutomo Sirait; Marlon Sihombing (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the influence of Job Stress and Job Insecurity on Turnover Intention at PT. Pelindo Multi Terminal. The influence of Job Stress and Job Insecurity will be analyzed partially and simultaneously on Turnover Intention. The form of research used in this research is quantitative research. The population in this study were employees of PT. Pelindo Multi Terminal, totaling 179 people, with a sampling technique using Simple Random Sampling with a sample size of 65. The results of the research show that Job stress and Job insecurity have a significant effect, both partially and simultaneously, on Turnover Intention at PT Pelindo Multiterminal. The coefficient of determination test shows that There is a close relationship between Job Stress and Job Insecurity with an R value of 0.633.